Las nuevas perspectivas regulatorias de delitos informáticos en las compras a través de internet - Verónica Liliana, Paguay Calderón (2021)
ABSTRACT With the evolution of technology and development of information technology in Ecuador, illicit and malicious acts sanctioned by the Comprehensive Organic Criminal Code have increased, such as: electronic fraud, electronic illegal appropriation, computer damage, etc .; acts performed by a person using a computer as a means to commit an offense. These criminal behaviors are known by the United Nations, by the European Union and of course in Ecuadorian law as computer crimes. Based on the foregoing, it is stated that the present investigation aims to identify what are the regulatory perspectives of computer crimes in purchases through the Internet; as new criminal behaviors have appeared that are committed through electronic commerce and that merit a practical theoretical analysis, in order to identify how the victims are being affected through the internet. To meet the objectives of the research, the synthetic analytical method has been used, which has allowed to identify and analyze the legal norms that are established in the Comprehensive Organic Criminal Code, as well as in the Law of Electronic Commerce, Signatures and Messages of text. Likewise, a practical case was analyzed that shows the violation of the rights of people who intervene in electronic commerce, which shows that the field of regulation of computer crimes in Ecuador should be expanded. Keywords: electronic commerce, cybercrime, fraud, Internet. .